The Dark Side of Entrepreneurship Education: A Delphi Study on Dangers and Unintended Consequences. (November 2021) - Bandera, Cesar; Santos, Susana C.; Liguori, Eric W.
While recent research explores the dark side of entrepreneurship there remains little exploration of what, if any, role entrepreneurship education (EE) plays in producing dark side outcomes. Accordingly, we explore dangers and unintended consequences EE poses to students and universities as well as the role of both student and instructor in mitigating dark side concerns. Specifically, we use a Delphi technique to distill from a panel of experienced educators the dangers EE may pose as well as strategies for mitigating dark side consequences. In sum, this work contributes to EE research by providing a unique mixed-methods view of the dark side of EE and raising awareness of the unintended consequences borne by the students and institutions we serve.